Pemanfaatan Kandungan Polifenol Ekstrak Daun Kersen (Muntingia calabura L.) Dalam Pengembangan Permen Jelly Fungsional Berbahan Buah Alpukat (Persea Americana Mill) - Nursan; Patang; Hambali, Amiruddin (Agricultural Technology Education Study Program, 2023)
Cherry is a plant that is easy to find with its fruit which is small and sweet. Cherry leaves are known to contain polyphenolic compounds, triterpenoids, tannins, saponins and polyphenols that act as antioxidant activity that can protect liver and body cell damage caused by free radicals. The purpose of this.study.was to determine the .effect.adding cherry leaf.extract to the quality and antioxidants of jelly candy and the response panelists to avocado jelly.candy.with the.addition of cherry .leaf.extract. This type of research is experimental-based quantitative with a completely randomized design (CRD) 4 treatments, namely: 0% (K), 1% (P1), 3% (P2) and 5% (P3). Parameters observed included water content, .ash content, .reducing.sugar, antioxidant activity, polyphenols and.organoleptic quality (color, taste, texture,.and.aroma). The data analysis.technique.used in this study.was.analysis variance (ANOVA) and Duncan's further test using.SPSS software version. 22. The.results showed.that the addition of 1%, 3%, and 5% cherry leaf extract had a significant effect on water content, .ash content, .reducing sugar, antioxidants, and polyphenols as well.as organoleptic.quality. The organoleptic.test of the parameters of color, taste, texture and aroma of jelly candy was the most preferred by panelists for the addition of 0% cherry leaf extract.